KINERJA MODEL PERKERASAN JALAN DENGAN BLOK PENGAKU - Marjono , (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
One of the factors causing the cracking of rigid pavement surfaces for roadways is the occurrence of tensile stresses due to vehicle wheel loads that exceed the tensile stresses of the concrete, if not handled immediately will affect the service life of pavement construction.This research is conducted to get alternative solution from pavement construction problem, that is damage before end of service period. One of the efforts that can be done is to make a model of pavement construction that can reduce the tensile stress on the underside of the concrete plate by adding a stiffening block on the underside of the concrete plate for road pavement. The results of this study are expected to be one form of innovation from rigid pavement construction that can be applied in Indonesia. On the basis of this then the researchers took the title